Desain Model Dan Strategi Keberlanjutan Wisata Pantai 9 Pulau Giligenting, Sumenep, Madura - Rakhmawati; Yudhi Prasetya Mada; Mokh. Rum (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The tourism sector contributes to Sumenep Regency's original regional income (PAD). Therefore, its development requires stakeholder intervention. Sustainability of tourism development at Gili Genting Island Beach, Sumenep Regency, Madura requires cooperation between actors in the Hexa Helix concept which consists of six elements, namely education, business, society, government, mass media and health. This research aims to formulate a model and strategy for sustainable development of Beach 9 tourism on Gili Genting Island, Sumenep Regency, Madura. The sustainability of the tourism sector is approached through ecological, socio-cultural, economic, religious and institutional dimensions. The research method uses mixed methods research, namely combining analytical hierarchy process (AHP) and qualitative descriptive methods. Data collection techniques were carried out using in-depth interviews